2016
DOI: 10.1186/s13075-016-1108-9
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab as monotherapy or combination therapy for treating active rheumatoid arthritis: a meta-analysis of efficacy and safety reported in randomized controlled trials

Abstract: BackgroundPrevious studies in patients with rheumatoid arthritis (RA) have shown that switching to tocilizumab (TCZ) monotherapy (TCZMONO) or combination therapy (TCZCOMBI) with conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) is efficacious in reducing disease activity in patients with inadequate response to csDMARDs. However, hitherto there is no consensus on whether TCZMONO is as effective as TCZCOMBI. The objective of this study was therefore to evaluate the efficacy and safety of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 45 publications
2
29
0
3
Order By: Relevance
“…No difference in the frequency of AEs was observed between patients who received TCZ monotherapy and those who received combination therapy. A meta-analysis of TCZ clinical trials [37] and the French real-world ACT-SOLO study [38] similarly found no difference in the frequency of AEs in patients receiving TCZ monotherapy vs. combination therapy. Rates of AEs and SAEs were numerically more frequent in biologic-exposed patients than biologic-naive patients.…”
Section: Discussionmentioning
confidence: 99%
“…No difference in the frequency of AEs was observed between patients who received TCZ monotherapy and those who received combination therapy. A meta-analysis of TCZ clinical trials [37] and the French real-world ACT-SOLO study [38] similarly found no difference in the frequency of AEs in patients receiving TCZ monotherapy vs. combination therapy. Rates of AEs and SAEs were numerically more frequent in biologic-exposed patients than biologic-naive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab is an interleukin-6 inhibitor with efficacy in treating RA in placebo-controlled randomized trials as monotherapy [7] and in combination with conventional disease-modifying antirheumatic drugs (DMARDs) [8,9]. This agent is effective and well tolerated during routine clinical care as intravenous (IV) or subcutaneous formulations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although tocilizumab and the TNF blockers are most commonly given in combination with methotrexate, a recent report suggested that tocilizumab was more efficacious than adalimumab (an anti-TNF) in RA patients when given as a monotherapy (27). Furthermore, tocilizumab is only marginally more effective when given in combination with methotrexate as compared with tocilizumab monotherapy (28). This may represent a significant advantage of tocilizumab treatment because many patients cannot tolerate side effects caused by methotrexate therapy.…”
Section: Discussionmentioning
confidence: 99%